Relationship between obsessive-compulsive disorders and diseases affecting primarily the basal ganglia - Maia, Alex S. S. Freire; Barbosa, Egberto Reis; Menezes, Paulo Rossi; Miguel Filho, Eurípedes C. (Revista do Hospital das Clínicas, 1999)
Obsessive-compulsive disorder (OCD) has been reported in association with some neurological diseases that affect the basal ganglia such as Tourette's syndrome, Sydenham's chorea, Parkinson's disease, and Huntington's disease. Furthermore, studies such as neuroimaging, suggest a role of the basal ganglia in the pathophysiology of OCD. The aim of this paper is to describe the association of OCD and several neurologic disorders affecting the basal ganglia, report the existing evidences of the role of the basal ganglia in the pathophysiology of OCD, and analyze the mechanisms probably involved in this pathophysiology.